Acceptance and Commitment Therapy versus Expressive Writing Therapy for Emotional Regulation and Emotional Numbing among Nursing Students - Rafi Jachra Adam; Sri Sumartini; Nadia Sintia Wardany; Slamet Rohaedi; Amelia Febrianti (Institut Kesehatan Suaka Insan, 2026)
Emotional numbing among nursing students can impair emotional regulation and increase vulnerability to psychological distress. This study aimed to compare the effectiveness of ACT and EWT in enhancing emotional regulation and reducing emotional numbing. A quasi-experimental pretest–posttest two-group design was conducted, involving 52 nursing students selected through purposive sampling and subsequently assigned to intervention groups primarily through random allocation. Emotional regulation was measured using DERS, while emotional numbing was assessed with the ERNS-G. Data were analysed using paired t-tests and ANCOVA to compare posttest outcomes while controlling for pretest scores. Both ACT and EWT significantly improved emotional regulation and reduced emotional numbing within groups (p < .05). However, ANCOVA revealed no statistically significant differences between ACT and EWT in emotional regulation (F = 1.373, p = .247, ?² = .027) or emotional numbing (F = 0.791, p = .378, ?² = .016) after controlling for pretest scores. Both ACT and EWT were effective in improving emotional regulation and reducing emotional numbing among nursing students. Nevertheless, no statistically significant difference in effectiveness was found between the two interventions.